Isolation and Antibiotic Susceptibility Patterns of Pseudomonas aeruginosa From the Patients with Respiratory Tract Infection - Riyam Wissam Hassan (Academia Open, 2026)
General Background: Respiratory tract infections caused by bacterial pathogens contribute significantly to global morbidity and mortality, with Pseudomonas aeruginosa being a major nosocomial pathogen frequently isolated from respiratory infections. This Gram-negative bacterium exhibits intrinsic antibiotic resistance and can develop multiple resistance mechanisms, making treatment increasingly challenging. Knowledge Gap: Although P. aeruginosa is recognized for multidrug resistance, periodic monitoring of antibiotic susceptibility patterns in specific geographic regions remains essential as resistance profiles vary temporally and geographically. Aims: This study aimed to isolate and identify P. aeruginosa from sputum samples of patients with respiratory tract infections and determine antibiotic susceptibility patterns against thirteen commonly used antibiotics. Results: Among 110 sputum samples collected from Al-Diwaniyah Teaching Hospital (March-July 2025), P. aeruginosa was isolated from 33.33% of culture-positive samples, demonstrating highest resistance to ceftazidime (76.92%), cefepime (73.07%), and levofloxacin (76.92%), while showing greater sensitivity to amikacin (61.53%) and colistin (53.84%). Novelty: This investigation provides current antibiotic resistance data specific to the Al-Diwaniyah region, revealing alarmingly high resistance rates to modern-generation cephalosporins. Implications: These findings necessitate updating regional antibiotic treatment protocols for respiratory infections and recommend amikacin-colistin combination therapy to mitigate further resistance development.Keywords : Pseudomonas Aeruginosa, Antibiotic Resistance, Respiratory Tract Infections, Antimicrobial Susceptibility, Multidrug ResistanceHighlight : P.aeruginosa accounted for 33.33% of bacterial respiratory tract infections studied. Highest resistance observed to Ceftazidime (76.92%), Levofloxacin (76.92%), and Cefepime (73.07%). Amikacin and Colistin demonstrated greatest effectiveness with 61.53% and 53.84% sensitivity rates.